Cultivation of Social Character Through Local Wisdom "Pamali" as the Basic Capital of Sustainable Development - Nashar Nashar; Erlina Wiyanarti (Journal of Social Studies Education, 2025)
This study elaborates on the local wisdom of pamali as a manifestation of unwritten cultural norms that represent prohibitions or taboos that apply in traditional societies. Pamali is believed to have metaphysical consequences if violated, which is often interpreted as the arrival of catastrophe. The main objective of this study is to reveal the philosophical and ecological dimensions of pamali culture and its relevance in strengthening social character and sustainable development. This study uses a qualitative descriptive approach with the literature study method as the main instrument for data collection. The results of the study show that pamali not only functions as a social control mechanism, but also as an educational tool that instills moral, spiritual, and ecological values to the next generation. In the context of sustainable development (Sustainable Development Goals), the values contained in the pamali tradition can be conceptualized as cultural capital that plays a strategic role in forming a collective awareness of the importance of environmental conservation. Therefore, the internalization of pamali values can be a cultural basis in building social character that is rooted in local wisdom and oriented towards ecological sustainability.